Pengembangan SDM dalam Mendukung Pembangunan Berkelanjutan Melalui Community Based Tourism di Kecamatan Plantungan Kabupaten Kendal - Sapta Yulinar Maulidya; Ratih Pratiwi; Mochammad Purnomo (Jurnal Iqtisaduna, 2022)
Plantungan District is one of the sub-districts in Kendal Regency which has a lot of diverse tourism potential. However, the potential in Plantungan District has not been fully managed optimally. Supported by phenomena in the field which show that the level of community welfare is still low with a total of 4,102 residents (BPS, 2019). This study aims to determine the potential and management of tourism in Plantungan District, analyze conditions and provide recommendations for improving community welfare through community-based tourism that supports sustainable development so that tourism impacts can be obtained in the long term. The method used in this research is descriptive qualitative with the help of SOAR analysis to think and formulate the right strategy according to the conditions that exist in the research location. The results of SOAR analysis resulted in several formulations of development strategies: 1) approach the government/private sector to provide financial support and human resource development; 2) conduct internal socialization of the potential of the region and the urgency of the tourism sector in the economy to increase public awareness; 3) Adding tourist attraction by utilizing local wisdom; 4) Education for local communities related to tourism; 5) Implementation of tourism area marketing strategies through social media/digital marketing; 6) Empowering the community to create a tourism value chain so as to encourage the community and regional economy; 7) improve access to tourist sites; 8) Overcoming barriers to tourism development; 8) Maintain facilities and add to the completeness of other tourism aspects (something to see, something to buy, something to do). The development strategy was then integrated with the establishment of a community-based sustainable tourism management organization in Plantungan District, Kendal Regency.